1977
DOI: 10.1177/25.9.333017
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of epidermal growth factor in mouse submandibular gland.

Abstract: The cellular and subcellular localization of epidermal growth factor in the submandibular glands of male and female adult mice was established by immunoperoxidase techniques. In light microscopic preparations epidermal growth factor was found exclusively in the granular convoluted tubules of the gland. The intensity of staining for epidermal growth factor varied from cell to cell, and some cells apparently were negative. The pattern of staining was similar in the glands of male and female mice; however, the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 0 publications
4
67
0
Order By: Relevance
“…In these hypertrophic GCT cells the amount of mK1 was decreased by the action of androgen. Slight and infrequent intercellular and intergranular variations in staining intensity have been reported for EGF, NGF, and renin in GCT cells (Gresik and Barka 1977;Gresik et al 1978a;Tanaka et al 1981;Kusakabe et al 1986), but not to the degree seen here for mK1. Moreover, these variations in immunostaining are not sexually dimorphic and are clearly different from the sexual variation in mK1 distribution.…”
Section: Discussionmentioning
confidence: 65%
“…In these hypertrophic GCT cells the amount of mK1 was decreased by the action of androgen. Slight and infrequent intercellular and intergranular variations in staining intensity have been reported for EGF, NGF, and renin in GCT cells (Gresik and Barka 1977;Gresik et al 1978a;Tanaka et al 1981;Kusakabe et al 1986), but not to the degree seen here for mK1. Moreover, these variations in immunostaining are not sexually dimorphic and are clearly different from the sexual variation in mK1 distribution.…”
Section: Discussionmentioning
confidence: 65%
“…The biological significances of rodent submandibular glands have been focused on the biological active polypeptide producing system in GCT cells which showed sex dimorphism (1,6,16,22,23). In postnatal salivary glands, GCT cells were not developed just after birth; GCT cells appeared at 15 to 20 days of age in the mouse and 30 to 40 days of age in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…GCT cells in the salivary glands are unique cells which markedly exist in the SMG in mature male mice, and secretory granules are the main source of salivary gland growth factors such as EGF and NGF (1,8,12). GCT cells in rodent SMGs were found in mice, rats and hamsters, and EGF also exists in the rat GCT cells, however, the biological roles of hamster GCT cells are not yet understood.…”
Section: Discussionmentioning
confidence: 99%
“…In GCT cells in murine SMGs (mouse, rat, and hamster) particular structures exist for biosynthesis and storage of salivary gland growth factors (EGF and NGF), renin, kallikrein and esteroprotease (1,7,8,12,18). The preceding papers have reported that ductal segments of hamster SMGs were crossreacted with mouse EGF (11) and slightly positive to keratin proteins from immunohistochemical method (20).…”
Section: Immunocytochemicalmentioning
confidence: 99%